2018
DOI: 10.1103/physrevd.97.023519
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the lensing figure of merit through higher order convergence moments

Abstract: The unprecedented quality, the increased dataset, and the wide area of ongoing and near future weak lensing surveys allows to move beyond the standard two points statistics thus making worthwhile to investigate higher order probes. As an interesting step towards this direction, we expolore the use of higher order moments (HOM) of the convergence field as a way to increase the lensing Figure of Merit (FoM). To this end, we rely on simulated convergence to first show that HOM can be measured and calibrated so th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 67 publications
1
21
0
Order By: Relevance
“…non-Gaussian) summary statistics, and whether we understand, at the same level as the two-point statistics, the non-trivial systematic effects in these higher-order statistics. Common higher-order statistics with weak lensing include shear peak statistics (Dietrich & Hartlap 2010;Kratochvil et al 2010;Liu et al 2015;Kacprzak et al 2016;Martinet et al 2018;Peel et al 2018;Shan et al 2018;Ajani et al 2020), higher moments of the weak lensing convergence (Van Waerbeke et al 2013;Petri et al 2015;Vicinanza et al 2016;Chang et al 2018;Vicinanza et al 2018;Peel et al 2018;Gatti et al 2020b), three-point correlation functions or bispectra (Takada & Jain 2003Semboloni et al 2011;Fu et al 2014), Minkowski functionals (Kratochvil et al 2012;Petri et al 2015;Vicinanza et al 2019;Parroni et al 2020), and machine-learning methods (Ribli et al 2019;Fluri et al 2018Fluri et al , 2019Jeffrey et al 2021). Many of these have recently been applied to data (Liu et al 2015;Kacprzak et al 2016;Martinet et al 2018;Fluri et al 2019;Jeffrey et al 2021), often performing well in terms of cosmological constraints.…”
Section: Introductionmentioning
confidence: 99%
“…non-Gaussian) summary statistics, and whether we understand, at the same level as the two-point statistics, the non-trivial systematic effects in these higher-order statistics. Common higher-order statistics with weak lensing include shear peak statistics (Dietrich & Hartlap 2010;Kratochvil et al 2010;Liu et al 2015;Kacprzak et al 2016;Martinet et al 2018;Peel et al 2018;Shan et al 2018;Ajani et al 2020), higher moments of the weak lensing convergence (Van Waerbeke et al 2013;Petri et al 2015;Vicinanza et al 2016;Chang et al 2018;Vicinanza et al 2018;Peel et al 2018;Gatti et al 2020b), three-point correlation functions or bispectra (Takada & Jain 2003Semboloni et al 2011;Fu et al 2014), Minkowski functionals (Kratochvil et al 2012;Petri et al 2015;Vicinanza et al 2019;Parroni et al 2020), and machine-learning methods (Ribli et al 2019;Fluri et al 2018Fluri et al , 2019Jeffrey et al 2021). Many of these have recently been applied to data (Liu et al 2015;Kacprzak et al 2016;Martinet et al 2018;Fluri et al 2019;Jeffrey et al 2021), often performing well in terms of cosmological constraints.…”
Section: Introductionmentioning
confidence: 99%
“…Two-point statistics fail to capture this non-Gaussian information and thus yield an incomplete description of the matter distribution at low redshift. To close this gap, the community has recently started to explore non-Gaussian cosmic shear estimators: for example weak-lensing peaks (e.g., Kruse & Schneider 1999, 2000Dietrich & Hartlap 2010;Kratochvil et al 2010;Fan et al 2010;Yang et al 2011;Maturi et al 2011;Hamana et al 2012;Hilbert et al 2012;Marian et al 2012Marian et al , 2013Shan et al 2014Shan et al , 2018Lin & Kilbinger 2015;Martinet et al 2015Martinet et al , 2018Liu et al 2015a,b;Kacprzak et al 2016;Petri et al 2016;Zorrilla Matilla et al 2016;Giocoli et al 2018;Peel et al 2018;Davies et al 2019;Fong et al 2019;Li et al 2019;Weiss et al 2019;Yuan et al 2019;Coulton et al 2020;Ajani et al 2020;Zürcher et al 2021), Minkowski functionals (e.g., Kratochvil et al 2012;Petri et al 2015;Vicinanza et al 2019;Parroni et al 2020;Zürcher et al 2021), higher-order moments (e.g., Van Waerbeke et al 2013;Petri et al 2015;Peel et al 2018;Vicinanza et al 2018;…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that combining the shear twopoint statistics with higher-order statistics of the convergence such as higher-order moments (Vicinanza et al 2018), Minkowski functionals (Vicinanza et al 2019), or peak counts (Liu et al 2015;Martinet et al 2018) allows breaking common degeneracies. The precision of the KS+ mass inversion makes the E-mode convergence maps a promising tool for such cosmological studies.…”
Section: Resultsmentioning
confidence: 99%